2017
DOI: 10.5433/1679-0359.2017v38n4supl1p2489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatment on physicochemical and rheological characteristics of natural yogurts

Abstract: The aim of this study was to assess the influence of heat treatment on physicochemical and rheological characteristics of natural yogurts, as well as the influence of lyophilization process on natural yogurts after reconstitution. In the first experiment, three yogurt treatments were processed, as follows: Treatment 1, yogurt produced with raw refrigerated milk; Treatment 2, yogurt produced with refrigerated pasteurized milk; and Treatment 3, yogurt produced with UHT (ultra-high temperature) milk, in addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
3
0
0
Order By: Relevance
“…The physicochemical properties of milk can be greatly affected by the thermal sterilization parameters of raw milk. Célia et al (2017) reported that the highest protein content was found in yogurt produced by pasteurized milk compared with UHT and raw refrigerated milk, which is agreement with our study. Because skim milk powder was added to S milk, the protein content of the S KWL was higher than H KWL.…”
Section: Effect Of Milk Types On the Physicochemical Properties Of Kwlsupporting
confidence: 93%
See 1 more Smart Citation
“…The physicochemical properties of milk can be greatly affected by the thermal sterilization parameters of raw milk. Célia et al (2017) reported that the highest protein content was found in yogurt produced by pasteurized milk compared with UHT and raw refrigerated milk, which is agreement with our study. Because skim milk powder was added to S milk, the protein content of the S KWL was higher than H KWL.…”
Section: Effect Of Milk Types On the Physicochemical Properties Of Kwlsupporting
confidence: 93%
“…The fat content in the dairy products is reported to be related to the lipolysis of fungi, especially Saccharomyces, which also was detected in the finished products of H KWL. Further, the difference of pH value was not significant in all samples, which was similar to a previous study (Célia et al, 2017).…”
Section: Effect Of Milk Types On the Physicochemical Properties Of Kwlsupporting
confidence: 91%
“…The fat content registered in this research reduced considerably in the yogurt formulations with a lower pH after the fermentation, while minor changes were registered in the protein content, indicating that no degradation was evident after fermentation (Table 4). Previous research indicated a reduction in both fat and protein content in the final product after fermentation [39]. Based on our results, the fat decreased in all formulations depended on the bacterial combinations used in the fermentation process.…”
Section: Protein and Fat Analysis In Probiotic Yogurt Formulationssupporting
confidence: 71%